Can Endoscopic Tympanoplasty Be a Good Alternative to Microscopic Tympanoplasty? A Systematic Review and Meta-Analysis - Sang-Yeon Lee; Doh Young Lee; Yuju Seo; Young Ho Kim (Clinical and Experimental Otorhinolaryngology, 2019)
Although efficacies and proportions of tympanoplasty performed via endoscopic ear surgery (EES) have gradually introduced, it remains unclear whether total EES is a good alternative to microscopic ear surgery (MES). Herein, we aimed to compare therapeutic effects of EES and MES in patients receiving tympanoplasty or myringoplasty. A search of MEDLINE, PubMed, and Embase databases was conducted to compare the efficacies of EES and MES. Two investigators independently reviewed all studies and extracted data with a standardized form. We assessed risk of bias and calculated pooled odds ratio (OR) estimates with a 95% confidence interval (CI). Thirteen studies (607 EES patients and 678 MES patients) met inclusion criteria for quantitative meta-analysis. In pooled analysis, those who undergo EES have 0.99 times the OR of graft success compared to those with MES (95% CI, 0.84 to 1.16; P=0.894). In qualitative analysis, comparable hearing improvement was observed between the two groups, despite inconsistent audiometric evaluation. The air-bone gaps (ABGs) improved 2.02 dB less in EES than in MES (mean difference of improvements of ABGs, 2.02; 95% CI, –3.84 to –0.20; P=0.029); however, substantial heterogeneity and publication bias limited the integrity of this analysis. Further, EES significantly decreased canalplasty rate, wound complications, and operation time, compared to MES. Moreover, patients receiving EES reported higher cosmetic satisfaction than patients receiving MES. EES can be a good alternative to MES in terms of comparable graft success rate and hearing outcomes in patients receiving tympanoplasty or myringoplasty. Moreover, EES was less invasive, resulting in higher cosmetic satisfaction, reduced morbidity, and shorter operation time. Our results may affect decision-making and outcome prediction in cases of EES; however, confirmation is needed to clarify potential bias.